Tear proteomics of orbital decompression for disfiguring exophthalmos in inactive thyroid-associated ophthalmopathy - Jiang, Lihong (Exp Ther Med, 2020)
The progress and achievements that have been made in tear proteomics in thyroid-associated ophthalmopathy (TAO) are critical for exploring the pathogenesis of TAO and investigating potential therapeutic targets. However, the tear proteomics of orbital decompression for disfiguring exophthalmos in inactive TAO have yet to be properly investigated. In the present study, orbital decompression was performed to repair disfiguring exophthalmos in patients with inactive TAO. Tears were collected before and after orbital decompression in patients with inactive TAO. Liquid chromatography with tandem mass spectrometry (LC-MS/MS) was performed to explore the changes in tear proteomics. Bioinformatics analyses were then employed to analyze the functions of the differentially expressed proteins (DEPs) identified by LC-MS/MS. The palpebral fissure height and exophthalmia area were significantly restored after 1 month of orbital decompression such that they approached the normal levels identified in healthy eyeballs. Among the 669 proteins identified by LC-MS/MS, 83 proteins were changed significantly between the preoperative and postoperative stages in inactive TAO patients and healthy control individuals. The DEPs were predicted to be involved in numerous signaling pathways. Bioinformatics analyses revealed that pathways associated with the immune system, metabolism, programmed cell death, vesicle-mediated transport, neuronal system and extracellular matrix organization may fulfill significant roles in orbital decompression in patients with inactive TAO. Taken together, these results provided a preliminary understanding of the mechanism of orbital decompression for disfiguring exophthalmos in inactive TAO patients.